Measurement and Evaluation of In-Core Gamma Heating in the McMaster Nuclear Reactor - ALQAHTANI, MOHAMMED (My University, 2021)
The emission of gamma radiation in nuclear reactors manifests itself as heat which may substantially impact irradiation applications and reactor safety. Evaluating this phenomenon can increase the efficiency and safety of the reactor and its irradiation materials. Calculating or predicting the gamma heating (GH) in a nuclear reactor is not a simple task, especially when not all parameters of the reactor are known. This dissertation incorporates various methods for verifying results, including operational data, calculations and measurements. The thesis is divided into five research chapters to illuminate uncharted areas for simulation codes and to better understand factors influencing the GH. Study 1 applies the overall system for calculation of reactors (OSCAR-4) code system to the McMaster Nuclear Reactor (MNR) for understanding and verifying core-follow calculations against the MNR operational data. Based on this understanding, the calculational scheme presented advances to the operational fuel management data by (i) embodying an axial U-235 distribution profile and (ii) including all fissile materials present in the core. Study 2 gives insight into the impact of control rods (CR) movement on axial fuel inventory using the OSCAR-4 and Serpent-2 simulation codes. This was done to study whether OSCAR-4 performs as well as the time-consuming Serpent-2 for core-follow calculations. It was found that averaging the CRs movement can precisely predict fuel inventory without requiring detailed CRs tracking. Study 3 focused on improving MNR fuel operational data which were subsequently used in both the OSCAR-4 and Serpent-2 simulation codes. This research emphasizes the importance of applying the fuel inventory correction factor to any MNR cycle to accurately predict the fuel inventory at any given stage of a cycle. Study 4 involved the experimental measurement of GH using the SCK-CEN gamma thermometer (GT) in three irradiation sites at 27 GH values. In addition, a Serpent-2 simulation was conducted to calculate the GH at the same 27 points with an understanding of uncertainties accompanied by the measurement. Similarly, MCNP-6 code was implemented with the same methodology used for both OSCAR-4 and Serpent-2 and showed a very good agreement with the reactor operation data and GH measurement. The computational tools program provided a good prediction and evaluation of the GH. Finally, study 5 expanded the evaluation and uncertainty quantification of the GH under several reactor core conditions and time-dependent sets. The measurements presented in this work indicate that, even over four years, the combined effects of fuel burnup and fuel management operations do not significantly change the GH level inside the beryllium site. This is likely due to the overall distribution of the MNR core configuration and fuel burnup.